Fixed-point square roots - Gan, Woon-Seng (2013)
Square root (SQRT) is a common arithmetic operation used in many DSP algorithms. In this paper, we evaluate square rooting methods suitable for implementation on fixed-point (FxP) DSP processors with a fast multiplying unit. The finite wordlength effect on the square rooting methods is highlighted, and it is shown that the theoretically derived convergence rate for the Newton-Raphson (NR) based square rooting methods are not suitable for FxP processor. Also, the most efficient methods for 8-bit and 16-bit FxP processors are identified.